Structure and floristic composition of the savannahs of the Nizanda region, Isthmus of Tehuantepec (Oaxaca), Mexico - López-Olmedo, Liliana I.; Pérez-García, Eduardo A.; Meave, Jorge A. (Instituto de Ecología, A.C., 2006)
Current knowledge about savanna vegetation in Mexico is still incomplete, and it is dominated by an ongoing debate over their natural versus anthropogenic origin. In this paper we provide a detailed structural and floristic description of the savannas of the Nizanda region (Oaxaca, S Mexico). Vegetation was sampled in 20 sites of 15 m2 each (totaling 300 m2). A total of 135 morphospecies were encountered, 86 of which could be determined to species level; they were distributed in 29 families and 68 genera. Leguminosae, Poaceae and Asteraceae were the families with the largest taxonomic richness. Total community cover was 200.7 m2, of which 69% was accounted for by grasses and sedges. Despite a clear dominance of Trachypogon spicatus (Berger-Parker Index = 0.82), this community had a relatively large diversity (log2 Shannon Index = 3.64). Life form spectrum showed a dominance of chamaephytes and hemicryptophytes, indicating a harsh environment. Notwithstanding the widespread occurrence of secondary vegetation and ruderal species in the region, the virtual lack of exotic species in these savannas, together with the presence of some endemics and the identity of the dominant species, strongly support the primary nature of this plant community.